The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.3892/or_00000372
|View full text |Cite
|
Sign up to set email alerts
|

Significance of DNA methyltransferase-1 and histone deacetylase-1 in pancreatic cancer

Abstract: Abstract. Epigenetic modifications play an important role during carcinogenesis. The main goal of this study was to examine expression levels of two critical enzymes, DNA methyltransferase-1 (DNMT1) and histone deacetylase-1 (HDAC1), by immunohistochemistry (IHC) in human pancreatic cancer and precancerous lesions: 20 foci containing normal ductal epithelial cells without an inflammatory background (DE), 30 containing ductal epithelial cells with an inflammatory background (DEI), 48 of pancreatic intraepitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In addition, they observed decreased levels of DNA methylation at candidate genes in the normal pancreas of DNMT1 hypomorphic mice (86). Moreover, the expression of DNMT1 protein increased with the development of pancreatic cancer from normal tissue to precancerous lesions (PanINs) and to cancer (PDAC) (106109). Clinic pathological analyses by Wang and colleagues suggested that PDAC patients with higher DNMT1 protein expression had an overall lower survival rate than those with lower expression.…”
Section: Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they observed decreased levels of DNA methylation at candidate genes in the normal pancreas of DNMT1 hypomorphic mice (86). Moreover, the expression of DNMT1 protein increased with the development of pancreatic cancer from normal tissue to precancerous lesions (PanINs) and to cancer (PDAC) (106109). Clinic pathological analyses by Wang and colleagues suggested that PDAC patients with higher DNMT1 protein expression had an overall lower survival rate than those with lower expression.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Clinic pathological analyses by Wang and colleagues suggested that PDAC patients with higher DNMT1 protein expression had an overall lower survival rate than those with lower expression. Moreover, higher DNMT1 expression correlated with advanced stages of the disease, reflecting the malignancy potential of PDAC (109). Recent studies examining DNMT mRNA expression in pancreatic cancer has also demonstrated that the levels of the three DNMTs increased with the development of pancreatic cancer from normal duct to pancreatic intraductal neoplasia and further to PDAC.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Pharmacological studies have shown that emodin exhibits anticancer effects in a number of human cancers (3). In addition, previous studies have shown that emodin exerts antiproliferative and apoptosis-inducing effects on cell lines derived from ovarian (4) and lung (5) cancer and leukemia (6). However, at present there is little information demonstrating the possible antiproliferative effect of emodin on colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Fluctuation of microtubule composition expression may lead to dynamic changes in microtubule and eventually alter the tumor response to paclitaxel. The increased expression levels of α-tubulin and βIII-tubulin, mutation of βI-tubulin or down-regulation of microtubule associated proteins (MAPs) can undermine the inherent stability of microtubules and reduce the efficacy of paclitaxel [5152]. In this study, decreased mRNA and protein expressions of α-tubulin and βIII-tubulin in tumor tissues were detected in each treatment group except the control group.…”
Section: Discussionmentioning
confidence: 82%